Awareness and Perceptions of Bahrain’s Governmental Health Insurance: A Cross-Sectional Study - Salim Hasan AL ARRAYED (Interdisciplinary Social Research, 2026)
Objective: This study aimed to assess public awareness, knowledge, and perceptions of Bahrain’s governmental health insurance program using a descriptive cross-sectional design. Design: A cross sectional study was conducted via a structured, self-administered questionnaire. Setting: Governmental health centers in Bahrain from August 2025 to January 2026. Main outcome measures: Public awareness, knowledge, perceptions, and preferences regarding Bahrain’s governmental health insurance scheme, and correlations among these variables using Pearson’s correlation. Results: Findings indicated low awareness, with only 36.6% having heard of the scheme and 28.4% knowing enrollment processes. Knowledge of coverage was limited, as 59.8% lacked insurance, and 69.6% were unable to explain benefits. Perceptions reflected dissatisfaction and distrust, with 67.6% reporting inadequate coverage and 73.7% expressing low trust. Nevertheless, 78.9% preferred governmental over private insurance, and perception was strongly correlated with preference (r = 0.571, p < 0.01), while other correlations were not statistically significant (p > 0.05). Conclusion: The study highlights the importance of public trust and targeted education. Policymakers should prioritize transparent communication, media campaigns, and digital outreach to enhance awareness, acceptance, and progress toward UHC in Bahrain.